Development and validation of a model for predicting survival of young larvae of Tribolium castaneum exposed to elevated temperatures during heat treatment of grain-processing facilities. (May 2017) - Bingham, Aaron C.; Subramanyam, Bhadriraju; Mahroof, Rizana; Alavi, Sajid
Abstract: Heat treatment involves raising the ambient temperature of grain-processing facilities to 50–60 °C for at least 24 h to manage stored-product insects. The young larvae (first instars) of the red flour beetle, Tribolium castaneum (Herbst), are the most heat tolerant stage at temperatures of 50–60 °C when compared to eggs, old larvae, pupae, and adults. A thermal death kinetic model was developed to predict survival of T . castaneum young larvae exposed to six constant elevated temperatures between 42 and 60 °C. The model was based on two non-linear relationships: 1) logarithmic decrease in survival of larvae as a function of time, and 2) logarithmic decrease in larval survival as a function of temperature. The model was validated with 12 time-dependent temperature datasets collected during actual heat treatments of pilot-scale flour and feed mills and a commercial grain-processing facility. The observed survival of larvae in plastic boxes/vials with flour was used to validate model predictions. The heating rate to reach 50 °C from the ambient temperature, among the 12 datasets ranged from 0.9 to 7.8 °C/h. The mean absolute deviation between observed and predicted larval survival for 10 of the 12 datasets ranged from 2.1 to 11.4%; for the other two datasets it was 16.2 and 18.3%. These results show that the thermal death kinetic model can be used to predict survival of young larvae of T . castaneum based on time-dependent temperature profile obtained at any given location during heat treatment of grain-processing facilities. Highlights: Young larvae of Tribolium castaneum are heat tolerant at temperatures between 50 and 60 °C. A thermal death kinetic model was used to predict survival of young larvae during heat treatment. The model was validated with 12 datasets collected during heat treatment of facilities. Predicted larval survival for 10 of the 12 datasets was within 2.1–11.4% of observed survival. Only the time-dependent temperature data are needed to predict larval survival.